2012
DOI: 10.3174/ajnr.a3076
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening the Argument for Rapid Brain MR Imaging: Estimation of Reduction in Lifetime Attributable Risk of Developing Fatal Cancer in Children with Shunted Hydrocephalus by Instituting a Rapid Brain MR Imaging Protocol in Lieu of Head CT

Abstract: BACKGROUND AND PURPOSE:Children with shunted hydrocephalus have been undergoing surveillance neuroimaging, generally in the form of head CT, for evaluation of ventricular size. As the life expectancy of these children has improved due to better shunt technology and medical care, risks related to the ionizing radiation incurred during multiple head CT examinations that they are expected to undergo throughout their lifetime have become a concern. The purpose of this study is to estimate the LAR of developing fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
47
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 19 publications
0
47
0
1
Order By: Relevance
“…Lowdose CT protocols have been used in some hospitals, including our own, following the principle of as low as reasonably achievable 16 ; however, children with hydrocephalus will have multiple neuroimaging studies throughout their lives, increasing their total lifetime radiation exposure and consequently having a greater lifetime risk of radiation-induced brain cancers. [5][6][7][8][9][10] Therefore, elimination of radiation-based imaging techniques whenever possible is critical to ensure the long-term health of this population. Highlighting this belief, Koral et al 7 recently found that there is an increased risk of developing fatal cancer if children with hydrocephalus undergo neuroimaging surveillance with head CTs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lowdose CT protocols have been used in some hospitals, including our own, following the principle of as low as reasonably achievable 16 ; however, children with hydrocephalus will have multiple neuroimaging studies throughout their lives, increasing their total lifetime radiation exposure and consequently having a greater lifetime risk of radiation-induced brain cancers. [5][6][7][8][9][10] Therefore, elimination of radiation-based imaging techniques whenever possible is critical to ensure the long-term health of this population. Highlighting this belief, Koral et al 7 recently found that there is an increased risk of developing fatal cancer if children with hydrocephalus undergo neuroimaging surveillance with head CTs.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9][10] Therefore, elimination of radiation-based imaging techniques whenever possible is critical to ensure the long-term health of this population. Highlighting this belief, Koral et al 7 recently found that there is an increased risk of developing fatal cancer if children with hydrocephalus undergo neuroimaging surveillance with head CTs. These and similar results have repeatedly been reported in the lay press, and as a result, both providers and patients' families are routinely demanding that radiation-free protocols be used whenever possible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Koral et al estimate the annual frequency of surveillance neuroimaging in this patient population to be approximately 2 CTs per year throughout a lifetime. 8 An individual patient in our study underwent 25 brain imaging studies during the 4-year study period, and 21 of these 25 imaging studies were QB-MRI studies. With an estimate of 2-5 mSv administered per brain CT, this child was spared 42-105 mSv of effective radiation dose during our study period alone through the use of QB-MRI.…”
Section: Discussionmentioning
confidence: 99%
“…8 Recent developments in MR pulse sequences now allow for rapid evaluation of ventricular size in the pediatric population without the need for sedation. [9][10][11][12][13][14] Although various techniques have been used, heavily T2-weighted single-shot fast spin-echo and gradient recalled-echo imaging are the 2 most common pulse sequence methods used to interrogate ventricular size and shunt catheter tip location, respectively. 15 Starting in April 2009, our institution introduced a similar T2-weighted HASTE rapid-sequence MR imaging protocol.…”
mentioning
confidence: 99%